Uncertainty and Bias in Global to Regional Scale Assessments of Current and Future Coastal Flood Risk. Issue 7 (20th July 2021) - Hinkel, J.; Feyen, L.; Hemer, M.; Le Cozannet, G.; Lincke, D.; Marcos, M.; Mentaschi, L.; Merkens, J. L.; de Moel, H.; Muis, S.; Nicholls, R. J.; Vafeidis, A. T.; et al.
Abstract: This study provides a literature‐based comparative assessment of uncertainties and biases in global to world‐regional scale assessments of current and future coastal flood risks, considering mean and extreme sea‐level hazards, the propagation of these into the floodplain, people and coastal assets exposed, and their vulnerability. Globally, by far the largest bias is introduced by not considering human adaptation, which can lead to an overestimation of coastal flood risk in 2100 by up to factor 1300. But even when considering adaptation, uncertainties in how coastal societies will adapt to sea‐level rise dominate with a factor of up to 27 all other uncertainties. Other large uncertainties that have been quantified globally are associated with socio‐economic development (factors 2.3–5.8), digital elevation data (factors 1.2–3.8), ice sheet models (factor 1.6–3.8) and greenhouse gas emissions (factors 1.6–2.1). Local uncertainties that stand out but have not been quantified globally, relate to depth‐damage functions, defense failure mechanisms, surge and wave heights in areas affected by tropical cyclones (in particular for large return periods), as well as nearshore interactions between mean sea‐levels, storm surges, tides and waves. Advancing the state‐of‐the‐art requires analyzing and reporting more comprehensively on underlying uncertainties, including those in data, methods and adaptation scenarios. Epistemic uncertainties in digital elevation, coastal protection levels and depth‐damage functions would be best reduced through open community‐based efforts, in which many scholars work together in collecting and validating these data. Plain Language Summary: One of the main impacts of climate change is sea‐level rise leading to more frequent flooding of low lying coastal areas through higher tides, storm surges and waves. In this context, assessments of current and future coastal flood risk at global to world‐regional scales are needed to inform policy decisions on greenhouse gas reduction targets and finance of adaptation and flood disaster risk reduction. A key requirement for such assessments is that they consider all major uncertainties in models, methods and data applied, because the failure to do so may lead to poor policy outcomes. So far, this key requirement has not been met. To address this limitation, this paper provides the first comparative assessment of uncertainties in global to world‐regional scale studies of current and future coastal flood risks based on the published literature. We find that globally, by far the largest uncertainty concerns how coastal societies will adapt to sea‐level rise, which can influence future flood risk by factors 20–27. Other large global uncertainties are associated with socio‐economic development, digital elevation data, greenhouse gas emissions, and ice sheet evolution, influencing global exposure and flood risk by factors of up to 2 to 6. Key Points: We present the first comparison of uncertainties in global to world‐regional scale assessments of current and future coastal flood risk The largest uncertainty relates to future coastal adaptation, which can influence future coastal flood risk by factors of 20–27 Uncertainties in socioeconomic development, elevation data, defense levels, emissions and ice sheets can affect risks by factors of 2–6